The funambulist pamphlets. - Lambert, Léopold (Funambulist papers ;, 2013)
The blog The Funambulist: Architectural Narratives, a daily architectural platform written and edited by Léopold Lambert, finds its name in the consideration for architecture's representative medium, the line, and its philosophical and political power when it materializes and subjectivizes bodies. If the white page represents a given milieu -- a desert for example -- and one comes to trace a line on it, (s)he will virtually split this same milieu into two distinct impermeable parts through its embodiment, the wall. The Funambulist, also known as a tightrope walker, is the character who, somehow, subverts this power by walking on the line. The Funambulist Pamphlets is a series of small books archiving articles published on The Funambulist, collected according to specific themes. These volumes propose a different articulation of texts than the usual chronological one. The eleven volumes are respectively dedicated to Spinoza, Foucault, Deleuze, Legal Theory, Occupy Wall Street, Palestine, Cruel Designs, Arakawa + Madeline Gins, Science Fiction, Literature, and Cinema.